A construção identitária dos resgatistas do Corpo de Bombeiros de São Paulo - Silva, Edna Barbosa da (2013)
It is a research that involves individuals immersed in the Firefighters Corp s military environment who demonstrate saving lives as the main task. Knowing the processes involving the professional choice of the military firefighters and understanding how the firefighter character is built considering the continuous exposure to human suffering were the goals established for the development of this research which had as a main stage the 17th Mogi das Cruzes City Firefighter s Brigade of the São Paulo State. Through the qualitative approach with the analysis of the data obtained from the interviews made, it was possible to understand which elements are present in the moment of the professional choice and the resources used by these individuals in the construction of the firefighter character. The training undertaken and the socialization that takes place among them were the main factor identified in the process of the professional identity construction